Mitigating effects and mechanisms of Tai Chi on mild cognitive impairment in the elderly - Wang, Xin; Si, Keyi; Gu, Wei; Wang, Xueqiang (Frontiers in Aging Neuroscience, 2023)
Mild cognitive impairment (MCI) is a major public health concern that endangers the health and decreases the quality of life of the elderly around the world. A recent clinical guideline recommends regular exercise to patients with MCI. Tai Chi, a form of moderate-intensity mind–body exercise, is particularly suitable for seniors. This review aims to summarize epidemiological studies related to the effects of Tai Chi on MCI in older adults and reveal the potential neural mechanisms. Evidence suggested that Tai Chi can improve cognitive functions and alleviate the accompanying symptoms of MCI in the elderly potentially by activating the expression of signals in different brain regions, altering the connectivity between them, increasing the brain volume, and modulating brain-derived neurotropic and inflammation factors. Studies comparing various types of Tai Chi may contribute to the identification of paradigms that have appropriate intensities and difficulty and exert good effects on elderly people with MCI. In addition, studies are warranted to determine the frequency and duration of training that can optimize the beneficial effects of Tai Chi on MCI.